John Locke and natural philosophy - Anstey, Peter R., 1962- (Oxford : Oxford University Press, 2011)
Peter Anstey presents an innovative study of John Locke's views on the method and content of natural philosophy. He argues that Locke was an advocate of the experimental philosophy: the new approach to natural philosophy championed by the scientists of the Royal Society who were opposed to speculative philosophy.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Locke, John, -- 1632-1704.; Philosophy of nature